Korelasi Antara Inflasi, Suku Bunga, dan Risiko Investasi Terhadap Return Saham - Rohman, Apriyana (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2024)
In a dynamic capital market environment, understanding the relationship between economic variables such as inflation, interest rates, and investment risk and stock returns is crucial for investors. Inflation and interest rates are often considered important factors that influence overall economic conditions, while investment risk is an equally significant consideration in making investment decisions. This research aims to investigate the correlation between inflation, interest rates and investment risk with stock returns. By understanding the relationship between these economic factors, it is hoped that it can provide investors with better insight in managing their investment portfolios. The method used in this research is descriptive statistical analysis and regression. Historical data on inflation, interest rates, investment risk and stock returns will be collected and analyzed to identify patterns and correlations between these variables. The results of the analysis show that there is a significant correlation between inflation, interest rates and investment risk and stock returns. These findings illustrate how changes in these economic factors can influence stock performance in the capital market.